Halimeda incrassata (Bryopsidales, Chlorophyta) in Rhodes, Greece, Eastern Mediterranean - KONDYLATOS, GERASIMOS; KALAENTZIS, KONSTANTINOS; GRATSIA, EIRINI; MAVROULEAS, DIMITRIOS; KASAPIDIS, PANAGIOTIS; TSIAMIS, KONSTANTINOS; KLAOUDATOS, DIMITRIS (Mediterranean Marine Science, 2023)
The first record of the tropical green seaweed Halimeda incrassata (Bryopsidales, Chlorophyta) in the Eastern Mediterranean Sea is presented, based on several thalli found in the stomach of a silver-cheeked toadfish (Lagocephalus sceleratus), collected off Plimmiri beach, Rhodes, Greece. Species identification was based on morphological and molecular identification using the tufA gene as a molecular marker. The finding comes 10 years after a report on the species in Mallorca (Western Mediterranean Sea), where H. incrassata has spread rapidly. The pathway of its introduction in the Eastern basin is unknown, although shipping or the aquarium trade could be involved in this new introduction. Further studies are necessary for visual documentation of the infested areas around Rhodes and assessment of its possible spread in the following years.